Osteoarthritis: aspects of pharmacotherapy - L. N. Denisov; A. I. Platova; I. V. Menshikova; A. M. Lila (Современная ревматология, 2018)
The main goal of management of patients with osteoarthritis (OA) is analgesic and anti-inflammatory therapy, deceleration of the progression of the disease, and improvement of quality of life. Fast-acting symptomatic drugs (analgesics and nonsteroidal anti-inflammatory drugs (NSAIDs)) and sustained-release structure-modifying drugs (chondroitin sulfate, glucosamine sulfate, their combination, piascledine, diacerein) are used to treat OA. The European Society for Clinical and Economic Aspects of Osteoporosis and Osteoarthritis (ESCEO)) has analyzed the proposals of a number of expert groups and elaborated a consensus on the management of patients with OA: it has recommended the use of sustained-release drugs just in early OA.The article gives the data of comparative studies of a new Russian chondroprotector, the active ingredient of which is a bioactive extract from small sea fish, which contains alflutop. It evaluates the analgesic and anti-inflammatory effects and acute and chronic toxicity on experimental animal models and the preliminary results of therapy with the new drug in patients with OA in the large and small joints.